Usability of Microsoft Teams and Stream in Nursing Education. Issue 10 (27th October 2022) - Hebert, Michael; Upshaw, Antionella; Rossie, Jennifer
Abstract : This manuscript presents a technology acceptance and usability evaluation of an online software platform utilized for educating nursing students. Online nursing education is a complex and multifaceted process requiring nurse educators to be competent in technical informatics. Increasingly, nurse educators are asked to transform the traditional face-to-face classroom to include remote or hybrid experiences with little or no formal training. The pandemic may have created an atmosphere of stress and confusion while forcing a transition to an online learning environment. Recent trends in nursing education call for the increased use of technology that enhances the learning experience and mimic clinical practice. As the pandemic's restrictions are removed, nursing education will continue to require technological innovations. Variables measured during the study were usability (System Usability Scale), perceived usefulness, and perceived ease of use. The results of the study suggest participants perceived Microsoft Teams and Stream as useful and easy to use. In this situation, the use of technology positively supported the teaching-learning process.